1996
DOI: 10.1136/oem.53.8.559
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dust related respiratory effects in Dutch and Canadian grain handling industries: a pooled analysis.

Abstract: Objectives-Four previously conducted epidemiological studies in more than 1200 grain workers were used to compare exposure-response relations between exposure to grain dust and respiratory health. Methods-The studies included Dutch workers from an animal feed mill and a transfer grain elevator and Canadian workers from a terminal grain elevator and the docks. Relations between forced expiratory volume in one second (FEVy) and exposure were analysed with multiple regression analysis corrected for smoking, age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The reasons for the lower overall prevalence of asthma in New Zealand farmers are likely, at least in part, to be accounted for by the healthy worker effect which is particularly strong for non-malignant respiratory disease [Pearce et al, 1988]. In particular, other studies have reported decreasing asthma prevalence with number of years worked in agricultural occupations [Peelen et al, 1996;Chan-Yeung et al, 1979]. This pattern was also found in the current study where a (nonsignificant) negative association with duration of employment and asthma was seen, independent of age.…”
Section: Comparison Of Farmers and Nonfarmersmentioning
confidence: 99%
“…The reasons for the lower overall prevalence of asthma in New Zealand farmers are likely, at least in part, to be accounted for by the healthy worker effect which is particularly strong for non-malignant respiratory disease [Pearce et al, 1988]. In particular, other studies have reported decreasing asthma prevalence with number of years worked in agricultural occupations [Peelen et al, 1996;Chan-Yeung et al, 1979]. This pattern was also found in the current study where a (nonsignificant) negative association with duration of employment and asthma was seen, independent of age.…”
Section: Comparison Of Farmers and Nonfarmersmentioning
confidence: 99%
“…More recently, evidence of airflow obstruction associated with lower levels of grain dust has emerged from a series of well-controlled epidemiological studies (most with measurements of exposure levels). 7,[66][67][68][69][70] These studies provide consistent evidence showing exposure-related airflow obstruction in nonsmokers and smokers. There is also evidence for a strong "healthy worker effect," favoring the least-affected individuals to remain in the exposed work force.…”
Section: Organic Dustsmentioning
confidence: 59%
“…82 Most of the epidemiological studies with detailed pulmonary function measurements showed chronic airflow limitation. However, some studies 7,52,66,70,83,84 found that exposure to both grain and wood dust induced changes in FVC equal to the reductions in FEV1, suggesting the possibility of alveolar duct or parenchymal involvement as well. Furthermore, some of the wood dust studies have implicated exposure to visible mold as well as dust in dose-response analyses.…”
Section: Organic Dustsmentioning
confidence: 99%
“…In workplaces where grain is handled, there is substantial evidence that workers develop respiratory symptoms related to high concentrations of dust micro-and macroparticulate fractions produced by various stages of the industrial process [22][23][24][25][26][27][28][29][30]. In particular, bioaerosols have been widely studied in different occupational and nonoccupational settings, such as bakeries and flourmills [31,32].…”
Section: Introductionmentioning
confidence: 99%